Hospital Patients towards Sustainable Health and Wellbeing: A Study of Satisfaction & Loyalty - Eunice Mareth Querol Areola; Josefina Cano; Fernando Trinidad; Samuel PD Anantadjaya; Amelia Naim Indrajaya (International Journal of Business Studies, 2026)
This mixed methods case study, the factors behind patient satisfaction and patient loyalty in a Level 3 private hospital located in Ermita, Manila, Philippines. The study draws from Wu’s (2011) integrated model and Parasuraman’s SERVQUAL framework, and looks at how Hospital Image, Service Quality (Tangibles, Reliability, Responsiveness, Assurance, Empathy) connect to Patient Satisfaction and Patient Loyalty. Insights were taken from both patients and hospital workers, so the interrelationships are seen from more than one side, not just one perspective. For the data, the researchers used an adapted 34 item questionnaire with 377 valid respondents (189 patients and 230 hospital workers) and it was complemented with in depth interviews. The statistical analysis, included descriptive statistics, Pearson correlation, independent samples t test, and Partial Least Squares Structural Equation Modeling (PLS-SEM). Overall, results showed very high ratings for all constructs. Patients also tended to rate things higher than hospital workers. In addition, all six relationship hypotheses (H01–H06) were supported strongly, with very strong positive correlations and significant path coefficients. Service Quality and Patient Satisfaction were found to partly mediate the relationship between Hospital Image and Patient Loyalty. The study also found perceptual gaps between patients and hospital workers (p = 0.001) and, to a smaller extent, between healthcare professionals and management (H07). The PLS-SEM model itself indicated an acceptable to good fit. The findings can help improve healthcare service quality, increase patient loyalty, and support sustainable health outcomes, consistent with SDG #3.